Heterogeneous Impacts of Trade Shocks on Workers - Patrick Arni; Peter H. Egger; Katharina Erhardt; Matthias Gubler; Philip Sauré (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper identifies the causal effects of trade shocks on worker outcomes. We exploit a unique setting based on three pillars: (i) a large, unanticipated appreciation of the Swiss franc in 2015, (ii) detailed data with firm-level exposure to trade via output markets (both domestic and foreign) and imported inputs (distinguished by their foreign labor content), which we match to (iii) worker-level panel data with rich information on labor-market outcomes. We find that increased competition in output markets induces negative effects on earnings for workers of affected firms. Conversely, a price drop of foreign inputs generates positive effects for workers of importing firms, but less so the higher the labor content of these imported inputs. All these patterns are consistent with a parsimonious model of task-based production. Moreover, positive and negative earnings effects are especially strong for workers in the lower tail of the within-firm wage distribution and, in particular, for workers who change their employer, pointing at involuntary (voluntary) job separations from firms that are negatively (positively) affected by the exchange rate appreciation.
Keywords: F14; F16; J46; 330; trade and labor; exchange rate shock; matched employer-employee data